Respiratory chain deficiency in nonmitochondrial disease. (June 2015) - Pyle, Angela; Nightingale, Helen J.; Griffin, Helen; Abicht, Angela; Kirschner, Janbernd; Baric, Ivo; Cuk, Mario; Douroudis, Konstantinos; Feder, Lea; Kratz, Markus; Czermin, Birgit; Kleinle, Stephanie; et al.
Abstract : Objective: In this study, we report 5 patients with heterogeneous phenotypes and biochemical evidence of respiratory chain (RC) deficiency; however, the molecular diagnosis is not mitochondrial disease. Methods: The reported patients were identified from a cohort of 60 patients in whom RC enzyme deficiency suggested mitochondrial disease and underwent whole-exome sequencing. Results: Five patients had disease-causing variants in nonmitochondrial disease genes ORAI1, CAPN3, COLQ, EXOSC8, and ANO10, which would have been missed on targeted next-generation panels or on MitoExome analysis. Conclusions: Our data demonstrate that RC abnormalities may be secondary to various cellular processes, including calcium metabolism, neuromuscular transmission, and abnormal messenger RNA degradation.